STRATEGI PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM MULTIKULTURAL DI PERGURUAN TINGGI BERBASIS PESANTREN - Jumari; Wahyuni, Sri; Djazilan, M. Sukron (IAIN Madura, 2025)
Multicultural Islamic religious education curriculum development as an effort to instill multicultural values in Islam that occurs in pesantren-based universities. This research aims to analyze the strategy of developing multicultural Islamic religious education curriculum, to interpret multicultural Islamic religious education in pesantren-based universities. This research uses a qualitative approach with the type of literature study. Data is obtained by collecting various literatures and analyzing accordingly. Analyzing involves data condensation, presentation, conclusion drawing, and verification. The results of this study provide knowledge that the strategy of developing a multicultural Islamic religious education curriculum in pesantren-based universities requires the participation of several parties who must cooperate with each other, understand each other, be open and fair. The focus is the development of pesantren-based colleges that are increasingly open to diversity in society